Penerapan Model Pembelajaran Bamboo Dancing Untuk Meningkatkan Kemampuan Berfikir Kritis Siswa Pada Mata Pelajaran PAI - Hayati, Mardia; Putri, Nindia (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2024)
content through the application of the fifth grade bamboo dance model at SDI Nurul Haq Tualang. The subjects in this research were one teacher and 18 class V students at SDI Nurul Haq Tualang. The object of this research is the bamboo dance learning model and students' critical thinking abilities. This can be seen from the fact that before the action, the students' critical thinking ability score reached an average of 58.61 with classical completeness of 16.67%. After taking corrective action in cycle I, students' critical thinking abilities increased with an average of 69.72 with classical completeness of 38.88%. After improvements were made in cycle II, students' critical thinking abilities increased with an average of 76.67 and classical completeness 83.33% in the medium category. This means that the specified indicators have been successful. Thus, it can be concluded that through the Bamboo dancing learning model in the science and science lesson content, it can improve students' critical thinking skills in class V of SDI Nurul Haq Tualang, Tualang District, Siak Regency.